KOMUNIKASI INFORMASI DAN EDUKASI (KIE) PENYAKIT LUMPY SKIN DISEASE (LSD) PADA KELOMPOK TERNAK SAPI PERAH - Eka Puji Dameanti, Fidi Nur Aini; Hendrawan, Viski Fitri; Oktanella, Yudit; Adrenalin, Sruti Listra; Amri, Indah Amalia; Kamulyan, Ujiati; Assifa Mardiyah, Fraya (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Lumpy Skin Disease is a smallpox disease on the skin caused by the Lumpy Skin Disease virus from the genus Capripox, family Poxviridae. The LSD virus is double a stranded deoxyribonucleic acid (DNA virus), has a lipid envelope, and replicates in the cytoplasm. This disease can infect cattle and buffalo, and give an economic impact on farmers. Information about LSD in Indonesia has not been published for a long time and has not been published enough, so the Faculty of Veterinary Medicine, Brawijaya University has taken the role of conveying information about LSD through Communication, Information and Education (KIE) media in order to increase awareness of the entry and spread of LSD in areas experiencing LSD outbreaks. The KIE activity was attended by 17 participants from the "Sukses Bersama" Dairy Cattle Group. The results obtained from KIE activities were an increase in participants' knowledge, known from the results of the pretest and posttest analysis. The highest average score before the presentation of the material, the teenage group respondents answered 10 questions correctly, the adult and elderly groups answered 11 questions correctly. Meanwhile, after the presentation of the material, the highest average of respondents in the teenage, adult and elderly groups answered 12 questions correctly. The participant's age influences the participant's ability to answer questions correctly.